EPISTIMOLOGI PARADIGMA DAN REVOLUSI ILMU PENGETAHUAN THOMAS KUHN - M. Dwi Rahman Sahbana (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2022)
This research was born based on the thinking of Thomas Kuhn with the concept of scientific revolution with the characteristics of new thinking and philosophical models in terms of the history of the birth of science and the philosophy of science. The research method that the author uses is a qualitative method with a library research approach. The data collection technique in this study is a documentation technique, namely by collecting important data and files that support research activities. The result of this research is that for Thomas Kuhn the history of science is a starting point in studying fundamental problems in scientific epistemology, because science is basically always marked by the strength of the paradigm and the subsequent scientific revolution. This phase is what Thomas Kuhn termed the historical phase of the birth of new science, starting with normal science, then anomaly and crisis occurred, after which the scientific revolution emerged as a form of the birth of new science. Thomas Kuhn's thoughts can be contextualized with the development of Islamic scholarship with the aim of building openness of Islamic thought to anomalies and crises as well as the emergence of a revolution in Islamic science so as to motivate the emergence of a new paradigm in the realm of Islamic scholarship